Performance analysis of communication model on position based routing protocol: Review analysis - Himawan, Hidayatulah; Hassan, Aslinda; Bahaman, Nazrulazhar (Slovene Society Informatika, 2022)
Research on the Vanet system has its own challenges and obstacles with the communication system between nodes being the main issue. Four categories in the Vanet system topology, namely position based routing protocols, broadcast based routing protocols, cluster based routing protocols and multicast/geocast routing protocols, have fundamental differences, especially in the concept of sending data and information between nodes. For this reason, in this study, the selection of standardization and integration of data delivery between nodes is of particular relevance. The ability to send data properly in busy and fast traffic conditions is another challenge. For this, there are many variables that must be considered to improve communication between nodes.